2017
DOI: 10.1509/jm.15.0074
|View full text |Cite
|
Sign up to set email alerts
|

Does it Pay to Recall your Product Early? An Empirical Investigation in the Automobile Industry

Abstract: Defective products are often recalled to limit harm to consumers and damage to the firm. However, little is known about why the timing of product recalls varies after an investigation is opened. Likewise, there is little evidence on whether recall timing affects stock markets. This study tests the effect of problem severity on time to recall, the role of brand characteristics in moderating this relationship, and the stock market impact of time to recall. The authors test the hypotheses on a sample of 381 recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 65 publications
5
84
1
Order By: Relevance
“…Swift recalls or the time firms take to recall a defective product from the marketplace has been studied by scholars. While consequences of time to recall on stock market performance of the firm has been found to be negative (Eilert et al, 2017;Wood et al, 2017), scholars have shown that time to recall is influenced by firm-level factors (e.g., type of defects, supply chain position, recall strategy, and external agency pressure) and crisis factors (e.g., severity) (Eilert et al, 2017;Hora et al, 2011;Ni and Huang, 2017). Country of origin of imported products and components also were found to impact recall timing decisions (Majid and Bapuji, 2018;Muralidharan et al, 2015).…”
Section: Background: Recall Behavior Of a Firmmentioning
confidence: 99%
See 1 more Smart Citation
“…Swift recalls or the time firms take to recall a defective product from the marketplace has been studied by scholars. While consequences of time to recall on stock market performance of the firm has been found to be negative (Eilert et al, 2017;Wood et al, 2017), scholars have shown that time to recall is influenced by firm-level factors (e.g., type of defects, supply chain position, recall strategy, and external agency pressure) and crisis factors (e.g., severity) (Eilert et al, 2017;Hora et al, 2011;Ni and Huang, 2017). Country of origin of imported products and components also were found to impact recall timing decisions (Majid and Bapuji, 2018;Muralidharan et al, 2015).…”
Section: Background: Recall Behavior Of a Firmmentioning
confidence: 99%
“…A few articles have also examined the antecedents of recalls, such as top management characteristics, governance, and plant operational parameters (Kashmiri and Brower, 2016;Shah et al, 2016). While these studies have greatly advanced our understanding of the causes and consequences of product recalls, prior research has not adequately examined product recall processes, i.e., actual recall behavior of a company during a recall crisis (Eilert et al, 2017;Ni and Huang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to Eilert, Kalaignanam, Jayachandran, Swartz &Tracey ( [116]), Company recalled there malfunctioned products in order to minimize harm to target consumers and also loss to the company. Thus Eilert et al, [116] in their study investigate the effects of product recall on the stock market as well as time for recalling the effected product.…”
Section: Product Harm Crisismentioning
confidence: 99%
“…Thus Eilert et al, [116] in their study investigate the effects of product recall on the stock market as well as time for recalling the effected product. Also there research investigated the moderating role of brand characteristics on the relationship between the time to recall damage product and its effects on stock market.…”
Section: Product Harm Crisismentioning
confidence: 99%
See 1 more Smart Citation